Innovative marketing approaches as triggers to rural tourism sustainability: an in-depth analysis to existing literature - Rodrigues, Sónia (2021)
Rural tourism has become a truly relevant economic activity, with visible impacts (social and economic) to regional and national development and overall sustainability. The sole characteristics of rural destinations make them extremely attractive to tourists that search for experiences away from the massified and more urban areas. Despite this increase in the demand, in order to remain competitive and trigger its development and ensure sustainability, rural destinations need to ensure a twofold approach, first continuously create innovative and engaging tourism experiences, and secondly implement continuously innovative marketing approaches. Hence, to fully understand the state of the art in what concerns the incorporation of innovation by rural tourism marketeers, a systematic literature review focused on that same topic has been performed, the achieved set of 66 articles has been thoroughly analysed, and multiple results of this procedure are presented.